Bluetongue virus serotype 27: Experimental infection of goats, sheep and cattle with three BTV‐27 variants reveal atypical characteristics and likely direct contact transmission BTV‐27 between goats. Issue 2 (15th December 2017) - Bréard, E.; Schulz, C.; Sailleau, C.; Bernelin‐Cottet, C.; Viarouge, C.; Vitour, D.; Guillaume, B.; Caignard, G.; Gorlier, A.; Attoui, H.; Gallois, M.; Hoffmann, B.; et al.
Summary: Bluetongue virus (BTV) hitherto consisted of 26 recognized serotypes, of which all except BTV‐26 are primarily transmitted by certain species of Culicoides biting midges. Three variants of an additional 27th bluetongue virus serotype (BTV‐27v01‐v03) were recently detected in asymptomatic goats in Corsica, France, 2014–2015. Molecular characterization revealed genetic differences between the three variants. Therefore, in vivo characteristics were investigated by experimental infection of a total of 15 goats, 11 sheep and 4 cattle with any one of the three variants in separated animal trials. In goat trials, BTV‐naïve animals of the same species were kept in a facility where direct contact was unhindered. Of the 15 inoculated goats, 13 and 14 animals were found positive for BTV‐RNA and antibodies (Ab), respectively, until the end of the experiments. Surprisingly, BTV‐Ab levels as measured with ELISA and neutralization test (SNT) were remarkably low in all seropositive goats. Virus isolation from whole‐blood was possible at the peak of viremia until 49 dpi. Moreover, detection of BTV‐27v02‐RNA and Ab in one contact goat indicated that—similar to BTV‐26—at least one of three BTV‐27 variants may be transmitted by contact between goats. In the field, BTV‐27 RNA can be detected up to 6 months in the whole‐blood of BTV‐27‐infected Corsican goats. In contrast, BTV RNA was not detected in the blood of cattle or sheep. In addition, BTV‐27 Abs were not detected in cattle and only a transient increase in Ab levels was observed in some sheep. None of the 30 animals showed obvious BT‐like clinical signs. In summary, the phenotypes observed for BTV‐27v01‐v03 phenotypes correspond to a mixture of characteristics known for BTV‐25 and 26.